(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This survey research was conducted to find out the Social Skills and Social Anxiety Levels of 2nd-year Psychology Students as Factors of Peer Group Participation in Bestlink College of the Philippines. A total of 75 respondents were selected through the use of simple random sampling. In this sampling method, each population member has an equal chance of being selected. Above all, social anxiety got the highest weighted mean of two-point seventy-six (2.76). The overall weighted mean has two-point sixty-four (2.64) with the corresponding interpretation of often. This means that most of the respondents are influenced by social skills, social anxiety, social anxiety levels, and strategies to deal with social anxiety. The study revealed that the respondents aged 20-21 years old had the greatest number of responses, and the majority of the respondents are female (69.33%) second-year psychology students. Based on the gathered results, 22.67% of the respondents stated that they have no trouble interacting with their peer group. Among the 75 2nd year psychology students, 40% are experiencing social anxiety when speaking in class, which you can see in the results, where the total mean of 3.02 shows how often this occurs. The study also revealed that the majority of the respondents react negatively to social anxiety; they often feel frustrated or irritated when they are anxious, and this often leads to ineffective peer group participation. Also, the study showed that ages 20-21 and 60% out of 75 respondents tend to interact with their peer group to overcome their social anxiety.